The Nexus of Biofuels Production and Consumption, Green Economic Growth and Environmental Degradation - Anggi Putri Kurniadi; Hasdi Aimon (An Overview on Business, Management and Economics Research Vol. 2, 2023)
The obeject of this study is to fill gaps in previous research by examining the determinants of biofuel production and consumption, green economic growth, and environmental degradation in six Asia Pacific countries (Australia, China, India, Indonesia, South Korea, and Thailand) from 2007 to 2020. Biofuel is considered pure and the easiest available fuels on planet earth. Biofuels are obtained from biomass like wood and straw, which are released by direct combustion of dry matter and convert into a gaseous and liquid fuel. Other sources include organic matter like sludge, sewage and vegetable oils matter, which can be converted into biofuels by a wet process like digestion and fermentation. A simultaneous panel model technique was applied in this investigation. The study’s key findings are organized into four analytical models. For starters, biofuel consumption, capital formation, labor, and foreign direct investment all benefit biofuel production. Second, biofuels production, FDI, GDP per capita, and trade openness all have a beneficial impact on biofuels usage. Third, whereas militarism has a detrimental impact on green economic growth, biofuel production, consumption, and technical innovation have a favorable impact. Fourth, biofuel production, consumption, green economic growth, and cleaner energy all have a negative impact on environmental deterioration, whereas population and poverty have a favorable impact. . Biofuels oil has great potential in supporting renewable energy development to increase green economic growth and reduce environmental degradation. Biofuel production and consumption, green economic growth, and environmental deterioration are four interconnected aspects that must be addressed in order to achieve sustainable development. As a result, if one of them experiences a difficulty, it will have an influence on economic activity and environmental circumstances. Thus, the production and consumption of biofuels are the primary steps in carrying out environmentally friendly economic activities, as indicated in the condition of green economic growth, where these three points reinforce one another in the form of positive impacts to minimize environmental degradation. As commercial operations become more sophisticated, biofuels oil will play a significant part in addressing the energy dilemma in the future.